Microwave-Assisted Synthesis of Some Potential Bioactive Imidazolium-Based Room-Temperature Ionic Liquids - Ahmed H. Albalawi; Wael S. El-Sayed; Ateyatallah Aljuhani; Saud M. Almutairi; Nadjet Rezki; Mohamed R. Aouad; Mouslim Messali (Molecules, 2018)
An environmentally-friendly and easy synthesis of a series of novel functionalized imidazolium-based ionic liquids (ILs) is described under both the conventional procedure and microwave irradiation. The structures of newly synthesized room-temperature ionic liquids (RTILs) were established by different spectral analyses. All ILs (1–14) were screened for their in vitro antimicrobial activity against a panel of clinically isolated bacteria. The results of the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) showed that some of the tested ILs are very promising anti-bacterial agents especially those containing an alkyl chain with a phenyl group (most notably 1, 2, 12, and 13).